A transdiagnostic examination of decreased intolerance of uncertainty and treatment outcome. Issue 1 (2nd January 2018) - Stevens, Kimberly; Rogers, Travis; Campbell, Moselle; Björgvinsson, Thröstur; Kertz, Sarah
Abstract: Intolerance of uncertainty (IU) is characterized by negative beliefs and reactions to uncertainty. IU is present in emotional disorders and may be a mechanism of change in treatment . There are two components of IU, prospective and inhibitory IU, that may be differentially associated with outcome. The current study tested associations between pre- and post-treatment changes in the components of IU, symptoms of anxiety and depression, and treatment outcome in a large diagnostically heterogeneous partial hospital sample. Results suggested that social anxiety disorder was associated with greater pre-treatment prospective and inhibitory IU scores than those without the diagnosis. Results also showed that inhibitory IU predicted change in anxiety and depression symptoms and prospective IU and depression reductions predicted improvements in overall psychological health and psychological inflexibility. Only change in depression predicted improvement in interpersonal relationships throughout treatment. Clinical and theoretical implications of the findings are discussed.